Bioelectric Impedance Analysis (BIA) of body fat and blood chemical measurement in type II diabetes mellitus patients with obesity - Jems K R Maay; Budi Kristanto; Kismiyati Kismiyati (Poltekkes Kemenkes Bandung, 2026)
Background: Excessive fat accumulation resulting from an imbalance between caloric intake and energy expenditure is the hallmark of obesity. The growing prevalence of obesity-associated T2DM has been attributed to changes in lifestyle patterns, sedentary behavior, and elevated anthropometric indicators, particularly BMI and waist circumference. Objective: This study aimed to analyze BMI and waist circumference among obese individuals with T2DM at Hamadi Health Center, Jayapura City. Methods: A case-control study was conducted involving 92 participants, consisting of 46 obese individuals with T2DM and 46 obese individuals without T2DM. Data were analyzed using the independent t-test for normally distributed variables and the Mann–Whitney test for non-normally distributed variables. Results: Significant differences were observed between the case and control groups in height (p=0.001), diastolic blood pressure (p=0.005), glucose level (p<0.001), triglycerides (p<0.001), HDL cholesterol (p=0.007), and insulin level (p<0.001). Conclusion: Obese individuals with T2DM exhibited significantly different metabolic and clinical profiles compared with obese individuals without diabetes. These findings emphasize the importance of metabolic monitoring and early risk assessment among obese populations.